Pharmacokinetics and Pharmacodynamics of Two Formulations of Pegylated Recombinant Human Granulocyte Colony‐Stimulating Factor in Healthy Chinese Subjects: An Open‐Label, Randomized, Parallel‐Design Bioavailability Study. Issue 3 (21st June 2020) - Hu, Chaoying; Ji, Bingxin; Hu, Xiao; Yang, Cuicui; Sun, Wanling; Zhao, Xiaowei; Li, Lin; Li, Xiaoying; Zhang, Lan
Abstract: Pegylated recombinant human granulocyte colony‐stimulating factor (PEG‐rhG‐CSF, pegfilgrastim) is a long‐acting derivative of recombinant human granulocyte colony‐stimulating factor with limited renal clearance and a longer half‐life. It is used for the prevention of febrile neutropenia, owing to its capacity to promote neutrophil recovery. In this study, the pharmacokinetics, pharmacodynamics, safety, and immunogenicity of 2 formulations of PEG‐rhG‐CSF were evaluated in healthy Chinese subjects. Twenty‐four male subjects who received a single dose of subcutaneous PEG‐rhG‐CSF 100 µg/kg were randomized to either treatment A (3 mg/mL) or treatment B (1 mg/mL). Noncompartmental pharmacokinetic parameters of PEG‐rhG‐CSF were derived from serum concentration‐time data. In addition, absolute neutrophil count (ANC) as a pharmacodynamic maker, immunogenicity through antidrug antibody testing, and safety were evaluated. The mean area under the concentration‐time curve from time zero to the last quantifiable concentration (AUC0‐t ) and the mean maximum concentration (Cmax ) of PEG‐rhG‐CSF after treatment A were 5070 ng·h/mL and 125 ng/mL, respectively; these values were comparable to those measured after treatment B (5340 ng·h/mL and 123 ng/mL, respectively). The mean value of area under the △ANC (baseline‐adjusted ANC)‐time curve and the maximum △ANC values were 4380 × 10 9 h/L and 33.1 × 10 9 /L, respectively, in the treatment A group, and 5170 × 10 9 h/L and 38.6 × 10 9 /L, respectively, in the treatment B group. The pharmacokinetic and pharmacodynamic profiles were similar for the 2 PEG‐rhG‐CSF formulations following a single dose of 100 µg/kg. The safety and immunogenicity profiles were also similar, with no significant differences. The dose adjustment of PEG‐rhG‐CSF was not considered necessary for formulation transformation.